2019
DOI: 10.5114/ms.2019.84053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Barrett’s oesophagus and oesophageal adenocarcinoma

Abstract: Barrett's oesophagus is a condition characterised by metaplastic changes in the oesophagus and is a precursor to oesophageal adenocarcinoma. Oesophageal adenocarcinoma is recognised as being responsible for an increasing number of cancerrelated deaths, especially in the western world. A deluge of risk factors have been described in the literature. Some of the important ones include gastroesophageal reflux disease, Helicobacter pylori infection, lifestyle factors like alcohol consumption, smoking, and dietary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Current epidemiological studies present a consistent, rapidly increasing incidence of EAC in the United States and most other western countries, especially among males, with an observed or estimated start between 1960 and 1990, while the incidence of esophageal squamous cell carcinoma is stable or declining in all racial groups [ 3 , 4 ]. The etiology of EAC is multifactorial, and Barrett’s esophagus (BE) is a premalignant lesion that is observed in the majority of patients with EAC, and carries a risk of eventual development of EAC that is up to 30- to 125-fold higher than that in patients without this condition [ 5 , 6 ]. Previous studies have identified several risk factors for the development of BE, including male sex, older age, smoking, white race, obesity, hiatal hernia, and gastroesophageal reflux disease (GERD) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current epidemiological studies present a consistent, rapidly increasing incidence of EAC in the United States and most other western countries, especially among males, with an observed or estimated start between 1960 and 1990, while the incidence of esophageal squamous cell carcinoma is stable or declining in all racial groups [ 3 , 4 ]. The etiology of EAC is multifactorial, and Barrett’s esophagus (BE) is a premalignant lesion that is observed in the majority of patients with EAC, and carries a risk of eventual development of EAC that is up to 30- to 125-fold higher than that in patients without this condition [ 5 , 6 ]. Previous studies have identified several risk factors for the development of BE, including male sex, older age, smoking, white race, obesity, hiatal hernia, and gastroesophageal reflux disease (GERD) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a recent review, oesophagogastric junction cancers were reported to have a mortality rate of 85%, so screening is vital for precaution of oesophagogastric junction tumours. Also, the 5-year overall survival rate in oesophagogastric junction (OGJ) tumours ranges from 23 to 38% [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%